2011
DOI: 10.1111/j.1467-8268.2010.00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Competition and Efficiency in the Banking Sector in South Africa

Abstract: We analyse the evolution of competition and efficiency of the banking sector in South Africa using firm-level data for the period 1999-2008. We adopt a three-step estimation approach. First, we measure efficiency using the data envelopment analysis (DEA) methodology. Second, we use the Panzar-Rosse approach to derive the H-statistic for competitive conditions in banking. In the third stage, we take into account the role of managerial ability in competition by re-estimating the Panzar-Rosse model, with the DEA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
60
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 26 publications
8
60
1
2
Order By: Relevance
“…Despite these important policy changes, there is a dearth of empirical evidence in the conduct and performance of banks in South Africa. Known empirical studies include Simatele (2015), Simbanegavi et al (2015), Mlambo and Ncube (2011) and Okeahalam (2001). Mlambo and Ncube (2011) also incorporate efficiency in their analysis.…”
Section: Banking and Competition In South Africamentioning
confidence: 99%
“…Despite these important policy changes, there is a dearth of empirical evidence in the conduct and performance of banks in South Africa. Known empirical studies include Simatele (2015), Simbanegavi et al (2015), Mlambo and Ncube (2011) and Okeahalam (2001). Mlambo and Ncube (2011) also incorporate efficiency in their analysis.…”
Section: Banking and Competition In South Africamentioning
confidence: 99%
“…As such many studies conducted in South Africa [Okeahalam (2001), Greenberg & Simbanegavi (2009), Mlambo & Ncube (2011),] have taken a keen interest on investigating the nexus between competition and bank performance.…”
Section: Brief Review Of Empirical Literaturementioning
confidence: 99%
“…An extensive body of theoretical and empirical studies has reported the significant role of bank competition in ensuring access to finance (Clarke et al, 2006;Lin et al, 2010;Love and Per´ıa, 2014;Mudd, 2013;Rice and Strahan, 2010;Tan, 2013), efficiency (Mlambo and Ncube, 2011;Ningaye et al, 2014;Pasiouras et al, 2009;PruteanuPodpiera et al, 2008) and stability Fu et al, 2014;Schaeck and Cih´ak, 2014;Ariss, 2010) in any economy. According to Casu et al (2015), competition is good for many reasons; it is an essential force in any economy, it encourages firms to be more efficient and provide better allocation of resources.…”
Section: Introductionmentioning
confidence: 99%